PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT PADA PT.TUNAS DWIPA MATRA CABANG PAREPARE - Arham Djauharuddin; Mulyana Machmud; Ulyana Muslimin; Aryuni Aryuni (AkMen JURNAL ILMIAH, 2020)
Quality of service can provide a strong impetus for customers to form a good relationship with the business entity. Customers assess a service quality not only based on the results of a service but also must take into account the service delivery process. Product quality is one of the factors that consumers consider in buying a product and in this case the company is required to provide quality service that is able to influence added value, so that it is different from the quality of competitor services so that service quality is one of the factors for consumer consideration before buying a product. This study aims to determine how much influence the quality of service and product quality on purchasing decisions Honda beat motorbikes at PT. Tunas Dwipa Matra, Parepare Branch. The analysis method used is descriptive analysis method and multiple regression analysis method. The results of this study indicate that overall or collectively there is an influence between the independent variables on the dependent variable